2013
DOI: 10.1186/cc13115
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of ADAMTS13 (a disintegrin and metalloprotease with thrombospondin type 1 repeats, member 13) deficiency in septic shock patients involves interleukin-6 and is not dependent on disseminated intravascular coagulation

Abstract: IntroductionADAMTS13 (a disintegrin and metalloprotease with thrombospondin type 1 repeats, member 13) deficiency has been reported in patients with sepsis but its clinical relevance and pathophysiology remain unclear. Our objectives were to assess the clinical significance, prognostic value and pathophysiology of ADAMTS13 deficiency in patients with septic shock with and without disseminated intravascular coagulation (DIC).MethodsThis was a prospective monocenter cohort study of patients with septic shock. Vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 55 publications
4
55
1
1
Order By: Relevance
“…The standard therapy of secondary TMA is treatment of the coexisting disease, completed by plasma therapy (infusions of fresh frozen plasma, or plasma exchange). Since relative ADAMTS13 deficiency was demonstrated to predict poor prognosis in sepsis and in the systemic inflammatory response syndrome (Hyseni et al, 2014;Martin et al, 2007;Peigne et al, 2013), as well as this was also observed in our study, plasma supplementation appears to be a rational approach. As reported by Schwameis et al (2015) in a recent review, the potential mechanisms behind the insufficient cleavage capacity of ADAMTS13 during inflammation may include exhaustion, inhibition, proteolytic degradation of the enzyme, and competition.…”
Section: Figsupporting
confidence: 78%
“…The standard therapy of secondary TMA is treatment of the coexisting disease, completed by plasma therapy (infusions of fresh frozen plasma, or plasma exchange). Since relative ADAMTS13 deficiency was demonstrated to predict poor prognosis in sepsis and in the systemic inflammatory response syndrome (Hyseni et al, 2014;Martin et al, 2007;Peigne et al, 2013), as well as this was also observed in our study, plasma supplementation appears to be a rational approach. As reported by Schwameis et al (2015) in a recent review, the potential mechanisms behind the insufficient cleavage capacity of ADAMTS13 during inflammation may include exhaustion, inhibition, proteolytic degradation of the enzyme, and competition.…”
Section: Figsupporting
confidence: 78%
“…Clemens et al [26] also demonstrated that low ADAMTS13 levels were associated with a significantly higher DIC-score, but Peigne [21] observed no correlation between ADAMTS13 deficiency and DIC.…”
Section: Discussionmentioning
confidence: 99%
“…Peigne et al [21] emphasized the role of ADAMTS13 as a prognosis factor in septic shock and Ono et al [22] described decreased ADAMTS13 levels in 109 patients with sepsis-induced disseminated intravascular coagulation (DIC). Recently, a meta-analysis [23] revealed three studies that showed ADAMTS13 was significantly lower in sepsis than other critically ill non-septic patients [14,19,24].…”
Section: Discussionmentioning
confidence: 99%
“…However, the incidence of severe ADAMTS13 deficiency in these conditions is uncertain. Some studies, covering hundreds of patients in total, report severe ADAMTS13 deficiency in ~9% of them, 3638 whereas others report no instances of severe ADAMTS13 deficiency. 39,40 Differences in the study populations, possibly the prevalence of liver failure, may account for the different results.…”
Section: Conditions Other Than Ttp That May Affect Adamts13mentioning
confidence: 99%